Literature Review: Does Covid-19 Affect Physical Conditions, Exercise Patterns, Nutrition and Psychological Athletes? - Taufiq Hidayat (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
Covid-19 affects various aspects of life, including sports and everything in it, including athletes. Physical conditions, training patterns/programs, nutrition, and psychological athletes are required to be well maintained even though there are obstacles during the covid-19 pandemic. This study aims to provide an overview of physical conditions, exercise patterns, nutrition/eating patterns, and the psychology of athletes during the pandemic based on the results of the analysis of published articles. The method used in this research is literature study or literature review. A literature study is a research design used in collecting data sources related to a topic. Data collection for the literature study was carried out using a database search tool to search for literature sources regarding physical conditions, training patterns and programs, nutrition/eating patterns, and psychological athletes during the COVID-19 pandemic. The results of the data set that match the criteria to be conveyed in this study are five articles in each sub-discussion, including reports that have been published nationally and internationally. The results of the literature review analysis are expected to be used as studies or information that can be used as a theoretical basis for further research in the attention of athletes, especially in physical conditions, training patterns/programs—nutrition/diet and psychology of athletes during the covid-19 pandemic.